The US Women's Struggle towards Gender Equality up to 1970s - Mouad ,Alouaoui; Fecih , Nour Eddine; Nebeg , Raouf (Faculty of Letters and Foreign Languages Department of English, 2017)
This research aims to examine the struggle of the US women throughout the ages. It will be based on gathered data and analysis of women’s struggle towards gender equality starting from the 16th up to the 20th century. Women’s situation has changed in regards to their roles in society. They fought together and gained the right to vote which opened a doorway to liberation. Women were subjugated since the early signs of creation. They had almost no rights to be mentioned and their lives were of inhuman conditions. In the 16thand 17thcentury, Europe wasn’t the right place for women; as they were seen as properties and regarded as servants created to fulfil men’s needs. A new hope was on the horizon which was the New World colonization. It gave people a glimpse of a new life and brand new chance for freedom. They rolled in those ships with the thousands and abandoned everything they had to arrive at the land of the dreams. Yet, after few years, the infection of the brutality and oppression followed them. Therefore, they had no other chance but to fight. The gathered data and the progress achieved through this research allowed us to comprehend that women were not absolutely idle during the ages of oppression as we first thought; very few of them actually stood up for themselves via literature. Although, their influence and effect to the public was of minimal consequence, they at least tried to make a difference. Fortunately, we have also found out that the new formed government indeed was a great opportunity for women. For they took advantage of the new hope, the fresh enthusiasm, and the will for a new and improved government free of all the oppression and segregation. Progressively, they started demanding for better lives. The 19th century was the starting point of the struggle, followed by a century of difficulties and achievements as well. Passing through all the hardships shaped the reality of the modern woman which is different than before. The modern woman has more rights and better position in society. All their efforts were rewarded with success. They became a bit more equal to men than they were before.